Purification, Characterization and Molecular Studies of Fructose-6-Phosphate Phosphoketolase (F6PPK) from Bifidobacteria - Daifalla Fandi, Khalid Ghazi (2001)
Fructose-6-phosphate phosphoketolase (F6PPK; EC 4.1.2.22) is the key enzyme in the fructose-6-phosphate shunt pathway of glucose metabolism which is apparently restricted to bifidobacteria. Despite the biological importance of this bacterial group and the heterogeneity of the enzyme from different species, F6PPK in itself has not been characterized in detail with respect to size, subunit number, steady kinetics and N-terminal sequence. F6PPK was extracted and characterized for the first time from Bifidobacterium asteroides (isolated from the intestine of honeybees; ATTC 25909). The enzyme was purified to homogeneity using acetone fractionation at 40-70% saturation followed by fast protein liquid chromatography (FPLC) on Mono-Q anion exchange and Superose 12 gel filtration columns. The intact enzyme has a relative molecular mass of 110 ± 5 kDa as estimated by gel filtration chromatography (Sephadex G-200), and a single band was obtained on nondenaturingP AGE. It was then shown to be that of F6PPK following elution from preparative polyacrylamid gel. Sodium dodecyl sulphate (SDS)-PAGE under nonreducing conditions revealed the presence of a single polypeptide of 110 ± 2 kDa. SDS-PAGE of F6PPK reacted with 2-mecaptoethanol revealed the presence of two polypeptides of 59 ± 1 and 53 ± 0.5 kDa, indicating a dimeric structure (α₁ β₁) with disulfide-linked subunits. The NH2-terminal amino acid of the a. chain was found to be methionine. The enzyme was stable at pH 4.5-8.0 with an optimum activity at pH 6.0. The enzyme was stable below 42°C and the optimum temperature was 30°C. The apparent Km value of the enzyme for fructose-6-phosphate was 14.1 mM. The purified enzyme has no apparent requirement for thiamine pyrophosphate as cofactors. The enzyme was inactivated by Hg2+ and recovered after addition of dithiothretol, indicating that sulfhydryl group was probably involved in the enzyme activity. The features of B. asteroides F6PPK showed marked differences from those previously reported from animal and human strains. F6PPK from Bifidobacterium longum (probiotic grade; BB536) was also purified to electrophoretic homogeneity using the same purification steps above. The purified enzyme had a molecular mass of about 300 kDa as determined by gel filtration on Superose 12. F6PPK migrated as a single electrophoretic band in nondenaturing polyacrylamide gel electrophoresis (PAGE). It is probably a tetramer containing two different subunits with molecular masses of about 93 ± 1 kDa and 59 ± 0.5 kDa, as determined by SDS-PAGE. The N-terminal amino acid sequences of the subunits were determined, and no significant similarity was found between the deduced amino acid sequences and those in the databases of EMBL and SWISSPORT, indicating that we may be reporting for the first time the partial sequence of F6PPK from two type strains of Bifidobacterium species. However, the Mr 59000 subunit of B. asteroides F6PPK showed a significant similarity (70%) with the corresponding subunit from B. longum species. Oligonucleotide probes which were designed based on the deduced N-terminal amino acids sequences were unable to detect the presence of F6PPK gene using dot blot and Southern blot of the total genomic DNA from different species of bifidobacteria and other bacterial strains. In addition, the genomic library of B. asteroides was constructed in BamHI-digested pUCI9 by using about 2 to 6-kb DNA fragments obtained by partial digestion of the total genomic DNA with BamHI. The transformed cells efficiency of E. coli XLI- blue carrying plasmids with genomic inserts was 1.1 x 104 cfu mrl, and this library may be a useful tool for fishing the gene encoding for F6PPK.